Development of a nomogram for femtosecond laser astigmatic keratotomy for astigmatism after keratoplasty. Issue 4 (April 2016) - St. Clair, Ryan M.; Sharma, Anushree; Huang, David; Yu, Fei; Goldich, Yakov; Rootman, David; Yoo, Sonia; Cabot, Florence; Jun, Jason; Zhang, Lijun; Aldave, Anthony J.
Abstract : Purpose : To develop a nomogram for femtosecond laser astigmatic keratotomy (AK) to treat post‐keratoplasty astigmatism. Setting : Three academic medical centers. Design : Retrospective interventional case series. Methods : A review of post‐keratoplasty femtosecond laser AK was performed. Uncorrected (UDVA) and corrected (CDVA) distance visual acuities, manifest refraction, and keratometry were recorded preoperatively and 1, 3, 6, and 12 months postoperatively. The location, length, depth, and diameter of the AK incisions were recorded, and the surgically induced astigmatic correction was related to these variables using regression analysis. Results : One hundred forty femtosecond laser AK procedures were performed after penetrating keratoplasty (PKP) (n = 129) or deep anterior lamellar keratoplasty (DALK) (n =11), with 89 procedures (80 PKP, 9 DALK) included in the analysis. The mean CDVA improved from 20/59 (0.47 logMAR ± 0.38 [SD]) preoperatively to 20/45 (0.35 ± 0.31 logMAR) postoperatively ( P = .013) (n = 46). The mean keratometric astigmatism decreased from 8.26 ± 2.90 diopters (D) preoperatively to 3.62 ± 2.59 D postoperatively ( P < .0001) (n = 89). The mean refractive cylinder decreased from 6.77 ± 2.80 D preoperatively to 2.85 ± 2.57 D postoperatively ( P < .0001) (n = 69). A nomogram for femtosecond laser AK to treat post‐keratoplasty astigmatism was generated using regression analysis. Conclusions : Femtosecond laser AK significantly improved UDVA and CDVA and significantly reduced keratometric astigmatism and refractive cylinder after keratoplasty. The nomogram generated should improve the accuracy of post‐keratoplasty femtosecond laser AK. Financial Disclosure : None of the authors has a financial or proprietary interest in any material or method mentioned.